A ruptured ectopic pregnancy with contralateral hematosalpinx: A case report (Tanzania Medical Journal, 2023)
IntroductionExtrauterine pregnancy accounts for 1-2% of all pregnancies. Of all extrauterine pregnancies, approximately 95% occur in the fallopian tube. However, the occurrence of bilateral ectopic pregnancy is rare with an incidence of 1 out of 1,589 ectopic pregnancies. The diagnosis and management of bilateral ectopic pregnancy pose a challenge due to its retrospective diagnosis based on Norris criteria and there is no standardized treatment guideline worldwide for its management.Case presentationA 28-year-old woman, gravida 3, para 2 living 2 at gestation age of 6 weeks by date and 8 weeks by transvaginal ultrasound presented with sudden onset of sharp right lower quadrant abdominal pain accompanied with vaginal bleeding. Upon evaluation, she was pale, tachycardic with abdominal muscle guarding, rebound tenderness with positive cervical motion tenderness and fullness of posterior fornix. Urine pregnancy test was positive and abdominal-pelvic ultrasound revealed an empty endometrial cavity with the right-side heterogenous ill-defined echo-complex adnexal mass measuring [35x40]mm with free fluid seen in the hepatorenal recess and splenorenal space, left adnexa could not be appreciated. The decision to perform an emergency explorative laparotomy was reached due to an acute abdomen. Intraoperatively, ruptured and actively bleeding right fallopian tube with a gestation sac and hematosalpinx on the left fallopian tube. Bilateral salpingectomy was performed and sent for histologic studies. Histopathological evaluation later revealed a presence of hemorrhage, necrosis, and few remnants of chorionic villi on the right side while contralateral fallopian tube had edematous stroma, congested vessels with accumulation of inflammatory cells features of chronic salpingitis. On the third day post-surgery she was fully recovered and was discharged home.ConclusionDiagnosis and treatment of a unilaterally ruptured ectopic pregnancy complicated by contralateral hematosalpinx are difficult. Such patients' care should be tailored to their specific needs, with a focus on their future fertility goals, patient safety, and the availability of necessary resources.